The ruin probabilities of a discrete time risk model with one-sided linear claim sizes and dependent risks. Issue 7 (3rd April 2018) - Liu, Rongfei; Wang, Dingcheng; Guo, Fenglong
ABSTRACT: This article investigates the ruin probabilities of a discrete time risk model with dependent claim sizes and dependent relation between insurance risks and financial risks. The risk-free and risky investments of an insurer lead to stochastic discount factors θ n n ⩾ 1 . The claim sizes are assumed to follow a one-sided linear process with independent and identically distributed (i.i.d.) innovations ϵ n n ⩾ 1 . The i.i.d. random pairs (ϵ n, θ n ) n ⩾ 1 follow a common bivariate Sarmanov-dependent distribution. When the common distribution of the innovations is heavy tailed, we establish some asymptotic estimates for the ruin probabilities of this discrete time risk model.